2020
DOI: 10.1111/tpj.15065
|View full text |Cite
|
Sign up to set email alerts
|

Systematic prediction of autophagy‐related proteins using Arabidopsis thaliana interactome data

Abstract: SUMMARY Autophagy is a self‐degradative process that is crucial for maintaining cellular homeostasis by removing damaged cytoplasmic components and recycling nutrients. Such an evolutionary conserved proteolysis process is regulated by the autophagy‐related (Atg) proteins. The incomplete understanding of plant autophagy proteome and the importance of a proteome‐wide understanding of the autophagy pathway prompted us to predict Atg proteins and regulators in Arabidopsis. Here, we developed a systems‐level algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Following topological network analysis [17,[35][36][37][38], we found that mRNAs have a significantly higher network degree and betweenness, while a lower transitivity than non-coding RNAs (Figure 1G),…”
Section: Identification Of Mrnas That Participate As Cernas In Socmentioning
confidence: 92%
“…Following topological network analysis [17,[35][36][37][38], we found that mRNAs have a significantly higher network degree and betweenness, while a lower transitivity than non-coding RNAs (Figure 1G),…”
Section: Identification Of Mrnas That Participate As Cernas In Socmentioning
confidence: 92%
“…As shown in Figure 7, autophagy is induced by autophagy-related proteins (ATGs) [298,299]. Information on the functions of individual ATGs were summarized in a review by Su et al (2020) [284].…”
Section: Control Of Autophagy By Aba and Ethylene Signalingmentioning
confidence: 99%
“…According to estimates from the American Cancer Society, 1 in 78 women will suffer from ovarian cancer. Furthermore, around 21,750 will be newly diagnosed and 13,940 will die from ovarian cancer in 2020 [2]. Epithelial ovarian carcinomas account for 90% of ovarian cancer cases and serous ovarian carcinoma (SOC) is thus far the most common subtype in epithelial ovarian carcinomas [3, 4].…”
Section: Introductionmentioning
confidence: 99%